Sedimentologia da Aloformação Paranavaí, Bacia Hidrográfica do Alto Rio Paraná (SP, PR E MS) - SALLUN, ALETHÉA ERNANDES MARTINS; SUGUIO, KENITIRO; SOBRINHO, JOSÉ MARIA AZEVEDO SOBRINHO MARIA AZEVEDO (Pesquisas em Geociências, 2008)
The Paranavaí Alloformation is composed of Quaternary colluvial deposits, that are irregularly distributed throughout the Upper Paraná River Hydrographic Basin. This unit overlies of the Cretaceous superimposed to the sedimentary rocks Bauru Supersequence and basalts of the Serra Geral Formation. This work aims to provide a better definition of the Paranavaí Alloformation throught sedimentological characterization and provenance studies of its sediments, through textural and mineralogical analyses.The Paranavaí Alloformation is constituted by colluvial deposits, mainly composed by unconsolidated reddish colour sands. The contacts between these deposits and the underlying rocks are unconformable and marked by ferricrete and/or stonelines. The ferricretes constitute irregularly aggregated, millimetric to centimetric nodules, which exhibit reddish brown roughly concentric structures, with high SiO2 contents. Fine to coarse, quartzose sands exhibit corrosion features (microfissures), filled by goethite (ferric hydroxide). These sediments present 17 textural classes, with dominance of sand and clayey sand. The heavy mineral content of the Paranavaí Alloformation can reach 21,4% in weight, when overling the Serra Geral Formation. Superabundant minerals zircon, tourmaline, staurolite, rutile, kyanite in fine to very fine sands include pyroxene, hornblende, garnet, epidote, anatase and fluorite, with scarce spinel, apatite, sillimanite, monazite, brookite and andaluzite. The Paranavaí Alloformation presents, in general, homogeneous textural characteristics, and are very similar to the substrate rocks, suggesting the Bauru Supersequence and the Serra Geral Formation as source rocks.